Inherited platelet function disorders - Gresele, Paolo; Falcinelli, Emanuela; Bury, Loredana (Hämostaseologie, 2016)
Inherited platelet function disorders (IPFDs) make up a significant proportion of congenital bleeding diatheses, but they remain poorly understood and often difficult to diagnose. Therefore, a rational diagnostic approach, based on a standardized sequence of laboratory tests, with consecutive steps of increasing level of complexity, plays a crucial role in the diagnosis of most IPFDs.In this review we discuss a diagnostic approach through platelet phenotyping and genotyping and we give an overview of the options for the management of bleeding in these disorders and an account of the few systematic studies on the bleeding risk associated with invasive procedures and its treatment.
Keywords: Bleeding; diagnostic algorithm; inherited platelet function disorders; prophylaxis and Treatment